2012
DOI: 10.5152/balkanmedj.2012.006
|View full text |Cite
|
Sign up to set email alerts
|

General or Local Anaesthesia in One-Day Thyroid Surgery-Does It Matter?

Abstract: Objective: We aimed to determine the safety and feasibility of general anaesthesia (GA) compared with local anaesthesia + Monitored Anaesthesia Care (LA+MAC) for One-Day Thyroid Surgery (ODTS); to assess patient and operator satisfaction with either of the anesthetic approaches. Material and Methods:We reviewed prospectively 130 patients who underwent ODTS from 2008 to 2011. 64 patients were operated on under GA and 62 -under LA+MAC. All variables of patient demographic characteristics, duration and type of op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 17 publications
1
8
0
2
Order By: Relevance
“…We did not compare our cases with thyroidectomy under general anesthesia, so we cannot be certain that local anesthesia with MAC is superior to general anesthesia during thyroidectomy. However, the incidence of postoperative complications was similar to that of general anesthesia or local anesthesia with MAC compared to previous studies [239]. …”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…We did not compare our cases with thyroidectomy under general anesthesia, so we cannot be certain that local anesthesia with MAC is superior to general anesthesia during thyroidectomy. However, the incidence of postoperative complications was similar to that of general anesthesia or local anesthesia with MAC compared to previous studies [239]. …”
Section: Discussionsupporting
confidence: 80%
“…Snyder et al [3], reported about patients who received local anesthesia with MAC and boluses of midazolam, propofol, or fentanyl citrate for supplemental analgesia. Another study administered incremental doses of midazolam and fentanyl citrate to patients under MAC with regional anesthesia only when required [2]. The total and maintenance doses of the drugs were not reported in either study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations